Antioxidative Activity of Flavonoids from Abrus cantoniensis against Ethanol-Induced Gastric Ulcer in Mice - Li, Hui; Song, Zi-Jing; Dai, Yan-Ping; Zhang, Su-Li; He, Xin; Guo, Chang-Run; Zhang, Wen-Jun; Wang, Jiao-Ying; Zhang, Chun-Feng; Wang, Chong-Zhi; Yuan, Chun-Su (Planta Medica, 2015)
The present study investigated the flavonoids from Abrus cantoniensis against ethanol-induced gastric ulcers in mice. The flavonoids from A. cantoniensis were extracted with ethanol and purified by macroporous resin and polyamide. The 2,2-diphenyl-1-picrylhydrazyl assay was used to measure the antioxidative activities in vitro. The ethanol-induced ulcer mouse model was used to evaluate the gastroprotective activities of the flavonoids from A. cantoniensis. In addition, a method was established to ensure accuracy for animal ulcer evaluation. The flavonoids from A. cantoniensis showed a strong free radical scavenging capacity with an IC50 of 43.83 µg/mL in the 2,2-diphenyl-1-picrylhydrazyl assay. At doses between 28.16–112.67 mg/kg, the flavonoids conspicuously reduced the ulcer index in ethanol-induced mice (p < 0.001). Significant differences were found in the levels of superoxide dismutase, catalase, glutathione, and myeloperoxidase in the stomach tissues between the flavonoids from the A. cantoniensis groups and the ethanol control group. The gastroprotective effect of the flavonoids from A. cantoniensis could be due to its antioxidative activity of the defensive mechanism. The data revealed that the flavonoids from A. cantoniensis could be a potential therapeutic agent for gastric ulcer prevention and treatment.
Keywords: Abrus cantoniensis; Leguminosae; flavonoid; antioxidant; gastroprotection; Image Pro-Plus